Separation of Kaolinite from Clay Minerals and Its Catalytic Activity in Transesterification Reactions - Rahayu, Rahayu; Nengsih, Zarnida Widia; Arief, Syukri; Rilda, Yetria; Alif, Matlal Fajri; Syukri, Syukri (Universitas Pendidikan Mandalika, 2024)
Kaolinite is a type of clay mineral that has the potential to be used as a heterogeneous catalyst in transesterification reactions. However, natural clay still contains a mixture of minerals that occur together. Therefore, as an effort to search for cheaper catalysts to reduce the price of biodiesel production, this study carried out the separation of kaolinite from natural clay and tested its performance as a catalyst in biodiesel production from Waste Cooking Oil (WCO). Separation of the kaolinite fraction was carried out with the help of NH4Cl as a dispersing agent. The main mineral composition of clay as quartz, kaolinite, montmorillonite and hematite. After the separation process, the crystallinity of the minerals experienced an increase marked by an increase in the intensity of several kaolinite peaks, namely in the 2θ 12.24° area from 103 to 108 and at 25.00° from 95 to 125. Thermal modification caused the loss of several kaolinite peaks in the area. 2θ 12.17°; 24.94° and 62.39°. The Si/Al ratio decreased after the fractionation and calcination processes. Average particle size of h-clay decreased from 27.61 µm to 21.09 µm in K-clay. The K-clay catalyst produced the highest conversion of palmitic acid at 42%, while c-K-clay produced the highest conversion of oleic acid and stearate at 30%. In addition, the density and water content of biodiesel catalyzed by K-clay and c-k-clay meet SNI standards. This finding has the potential to be further developed as a cost-effective catalyst based on natural resources in biodiesel production.